Terapi Aktivitas Kelompok Tebak Gambar Dan Senam Hipertensi Dalam Mengatasi Penurunan Fungsi Kognitif Pada Lansia Dengan Gangguuan Sistem Kardiovaskuler : Hipertensi - Alfika Safitri; Erna Susanti; Ainul Latifah; Ayu Aulia; Ragita Citra Adzani Putri; Fauzi Rakha Riqy Putra Sulistyo; Sindri Disti Sagitri; Siti Nurbaidilah; Septa Yundari; Siti Hapsah; Naditiya Rahmawati; Waspah Pitriyah; Via Fauzia; Siti Hayatun N (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Introduction hypertension is a condition where blood pressure increases beyond normal limits. normal blood pressure limits vary according to age. Hypertension gymnastics is a sport whose one aim is to increase blood flow and oxygen supply to the active muscles and skeleton, especially to the heart muscle. The purpose of this hypertension exercise is to increase the knowledge of the elderly in the Tresna Werdha Budi Mulia 2 social institution regarding hypertension exercise to reduce blood pressure. The method used is by socializing and providing counseling and displaying posters containing the steps in hypertension exercise. The health counseling was held on Thursday, June 8 2023. The population in this counseling were the elderly in the Tresna Werdha Budi Mulia 2 Social Institution. After carrying out Health Education on hypertension exercises, the results (100%) were that the elderly in the Tresna Werdha Budi Mulia 2 Social Institution understood, understand and be able to give an example of how hypertension exercises to lower blood pressure.